Personal Journal of Applied Linguistics Tenses Mistakes of the 10th Grade Students in Writing Recount - Rohimah, Rohimah (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2019)
Recount is one of topic taught for the 10th grade students of senior high school include at Senior High School 1 South Tangerang City. And it is certain that the same topic will be taught again at the next level namely at 11th and 12th either just to repeat or to examine the student English knowledge or skill. Thus the students should be capable of recount in order to pass this topic well to achieve passing grade score. However, there are half of the class couldn’t get passing grades in writing recount text. Hence the writer was interested to do mini research to get reality why a half of the class didn’t pass on test of writing recount. Then the writer did the research to 18 participants. The research is by assigning 18 participants to write their activities or experiences that they did during holiday when the 12th grade students were doing the final examination with clear instruction and theme. The result was that most of participants have done many mistakes in using verbs, one of the language features that is along with the recount text is. In writing recount there are still many participants which use present verbs to tell the past activities and experiences. There are two past forms to concern in writing recount, they are linking verbs and action verbs. Linking verbs comprises was, were, saw, heard, etc; while action verbs are like went, looked, ran, sat, visited, sang, etc. Therefore this case must be an important note for every English language teacher in teaching recount. This is very important in order to avoid the mistakes in tenses of the use of both linking verbs and action verbs for the students when they are tasked to a project in composing recount text.